ANALISIS KESIAPAN PEMERINTAH DAERAH DALAM MENERAPKAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL DAN DAMPAKNYA TERHADAP SUMBER DAYA MANUSIA PADA PEMERINTAH KOTA BITUNG - Humiang, Greaty Prilen; Saerang, David P.E.; Karamoy, Herman (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
This study aims to determine the readiness of the government of Bitung in implementing accrual-based government accounting standards. Data was collected by observation at every SKPD in Bitung City Government followed in-depth interviews with key informants. The data collected was analyzed by qualitative methods. Then based on interviews (Focus Group Discussion) drawn conclusions indicate that Bitung City Government was ready to apply Accrual Based Government Accounting Standards. This is supported by the Government regulations which require to all local governments, including the city of Bitung in applying Accrual Based Government Accounting Standards, as well as Bitung City Government has issued the relevant mayor Accounting Policies in Bitung. Other things that support the readiness of the implementation of Accrual Based Accounting Standards, namely; development of human resources employee, committed leader who supports the changes later infromasi facilities and infrastructure systems are adequate and can accommodate Accrual Based Accounting Standards.